If it’s not on Strava, did it even happen? a running commentary on the blending of online and offline worlds, community building through digital platforms, and navigating authenticity in fitness spaces - Dabalos, Jedn Josh T.
This study investigates how the users of the digital platform Strava shapes‬Filipino runners’ engagement within hybrid fitness communities, blending online and‭ offline experiences. Motivated by existing literature on digital hybridity, community‬ building, and authenticity, the research addresses gaps concerning how digital platforms‬influence fitness culture in the Philippine context. The objective is to understand how the‬ users balance physical activities and online interactions to foster motivation,‬ accountability, and social connection. Using a qualitative approach, semi-structured‬ interviews were conducted with seven Filipino Strava users involved in formal and‬ informal running groups. Thematic analysis was applied to identify patterns related to‬ community dynamics, identity negotiation, and performativity in fitness spaces. Findings‬ demonstrate that Strava facilitates hybrid spaces where physical runs are digitally shared‬ and socially reinforced, allowing users to construct authentic yet curated selves.‬ Participants experienced increased motivation and a sense of belonging, mediated by‬ platform affordances and cultural factors. However, users also navigated privacy and‬ social comparison challenges. This study contributes to understanding technology’s role‬ in mediating contemporary fitness communities and highlights the evolving nature of‬ social connections in digital-physical hybrid environments within Philippine society.‬